Protective Effect of Hydroxytyrosol Against Oxidative Stress Induced by the Ochratoxin in Kidney Cells: in vitro and in vivo Study - Crupi, Rosalia; Palma, Ernesto; Siracusa, Rosalba; Fusco, Roberta; Gugliandolo, Enrico; Cordaro, Marika; Impellizzeri, Daniela; De Caro, Carmen; Calzetta, Luigino; Cuzzocrea, Salvatore; Di Paola, Rosanna (Frontiers in Veterinary Science, 2020)
Ochratoxin-A (OTA) is a mycotoxin that is a common contaminant of food products both for human and animal. This mycotoxin has several toxic effects. In particular, ochratoxin has significant nephrotoxic potential. In fact, OTA has been described to be responsible for naturally occurring animal and human kidney disorders. The toxicity of this mycotoxin involve the induction of oxidative stress pathway. Therefore, in the present study, we wanted to evaluate the potential protective effects of hydroxytyrosol (HT), a phenolic constituent with potent antioxidant activity, of extra virgin olive oil in three different renal cell lines, the Madin-Darby canine kidney cell line (MDCK), a pig kidney cell line (LLC-PK1) and a rabbit kidney cell line (RK 13), and in rats. Our results clearly showed that renal cells respond to OTA exposure by reducing both the induction of oxidative stress and cell proliferation. Pre-incubation of the cells with HT prevented cellular cytotoxicity and increased ROS levels induced by OTA. In addition, the antioxidative activity of HT was studied by measuring malondialdehyde (MDA) and lactate dehydrogenase (LDH) levels and nitrosative stress. Finally, we investigated the capability of HT (20mg\kg i.p.) to act in vivo. In rats, HT reduced oxidative stress and collagen accumulation in the kidney and counteracted the augmentations in AST, ALT and creatinine levels following OTA induction (250g\kg, for 90 days o.s.). In conclusion, our findings demonstrate that HT is able to protect three renal cell lines from damage induced by OTA and protect the kidneys of rats. Therefore, this compound could be an important strategy for the treatment and prevention of this type of kidney dysfunction.